Template mediated protein self-assembly as a valuable tool in regenerative therapy. (10th April 2018) - Kundu, B; Eltohamy, M; Yadavalli, VK; Reis, RL; Kim, HW
Abstract: The assembly of natural proteinaceous biopolymers into macro-scale architectures is of great importance in synthetic biology, soft-material science and regenerative therapy. The self-assembly of protein tends to be limited due to anisotropic interactions among protein molecules, poor solubility and stability. Here, we introduce a unique platform to self-immobilize diverse proteins (fibrous and globular, positively and negatively charged, low and high molecular weight) using silicon surfaces with pendant –NH2 groups via a facile one step diffusion limited aggregation (DLA) method. All the experimental proteins (type I collagen, bovine serum albumin and cytochrome C) self-assemble into seaweed-like branched dendritic architectures via classical DLA in the absence of any electrolytes. The notable differences in branching architectures are due to dissimilarities in protein colloidal sub-units, which is typical for each protein type, along with the heterogeneous distribution of surface –NH2 groups. Fractal analysis of assembled structures is used to explain the underlying route of fractal deposition; which concludes how proteins with different functionality can yield similar assembly. Further, the nano-micro-structured surfaces can be used to provide functional topographical cues to study cellular responses, as demonstrated using rat bone marrow stem cells. The results indicate that the immobilization of proteins via DLA does not affect functionality, instead serving as topographical cues to guide cell morphology. This indicates a promising design strategy at the tissue-material interface and is anticipated to guide future surface modifications. A cost-effective standard templating strategy is therefore proposed for fundamental and applied particle aggregation studies, which can be used at multiple length scales for biomaterial design and surface reformation.